Alpha-Arbutin Promotes Wound Healing by Lowering ROS and Upregulating Insulin/IGF-1 Pathway in Human Dermal Fibroblast - Polouliakh, Natalia; Ludwig, Vanessa; Meguro, Akira; Kawagoe, Tatsukata; Heeb, Oliver; Mizuki, Nobuhisa (Frontiers in Physiology, 2020)
Alpha-arbutin is known to inhibit tyrosinase, that converts tyrosine to melanin in keratinocytes. Here, we investigated alpha-arbutin antioxidant activity on human dermal fibroblasts essential for skin renewal and proliferation. We incubated human dermal fibroblast cultures for 48 hours with alpha-arbutin to observe changes in gene expression. Oxidative stress pathway genes common with genes induced by hydroquinone turned to be up-regulated by alpha-arbutin, and NRF2 mediates this response. Additional investigations on MMP3, EGFR, FOXO1, COL1A1, SIRT1, IGF1R, and ELOVL3 genes showed the potentiality of alpha-arbutin in wound healing and IFG1R pathway activation. We further conducted in silico phylogenetic footprinting analysis of promoter regions. These results suggested that transcription factors that are involved in tumor suppression and toxicity response. Our results support the idea that alpha-arbutin is the potent ingredient that protects the skin from the damage of sun radiation leading to inflammation and premature aging.